A comprehensive review on high-temperature fuel cells with carbon capture. (1st October 2020) - Wang, Fu; Deng, Shuai; Zhang, Houcheng; Wang, Jiatang; Zhao, Jiapei; Miao, He; Yuan, Jinliang; Yan, Jinyue
Highlights: High-temperature fuel cells as CO2 concentrators are presented. Developments of high-temperature fuel cell integrated CO2 capture processes are reviewed. Technical and economic evaluations on fuel cell hybrid systems with CO2 capture are discussed. Challenges and future prospects of fuel cell with CO2 capture are suggested. Abstract: High-temperature fuel cells and their hybrid systems represent one of the most promising technologies with high conversion efficiency. The configuration of such kind of system could facilitate an easy capture of CO2 . Several novel CO2 capture strategies have been developed based on high-temperature fuel cells, such as solid oxide fuel cell (SOFC), molten carbonate fuel cell (MCFC) and direct carbon fuel cell (DCFC). However, related review which focus on their system integration and performance evaluation is still rare. The aim of this study is to improve interest in high-temperature fuel cell with CO2 capture by providing an overview of the status of such kind of cutting-edge technologies. To approach this goal, the major strategies and technologies for fuel cells and their hybrid system with CO2 capture have been reviewed. Simultaneously, the characteristics of fuel cell technologies are summarized and the technical and economic performance of the fuel cell with CO2 capture are explored and discussed as well. The existing challenges that required to be overcome in fuel cell with CO2 capture technology are highlighted with aspects on fuel cell module scale-up, cost, safety, reliability and capture energy, etc. Finally, opportunities for the future development of high-temperature fuel cell with CO2 capture technologies are discussed. The conclusion remarks of this investigation indicate that fuel cell integrating CO2 capture process is a promising route to sustainable future, and could even be more effective if fuel cell technology can be commercialized.